Effectiveness of Mobile-Based Health Interventions for the Management of Hypertensive Patients: A Systematic Review - superzeki Zaidatul Fadilah; Ika Adelia Susanti; Dwi Yoga Setyorini; Rifky Octavia Pradipta (Universitas Airlangga, 2020)
Introduction: Cardiovascular disease is one of the biggest causes of death in the world. Hypertension is known as a major risk factor for morbidity and mortality in cardiovascular disease. Adherence to treatment is very important to overcome the problem, prevent complications, and prevent prolonged hospitalization in hypertensive patients. With the ever increasing technological development and the popularity of the use of internet-connected cellphones among the public, mobile-based and internet-based health interventions can be the right choice for the management of hypertensive patients. This study aimed to conduct a systematic review of the effectiveness of health interventions based on mobile health interventions for the management of hypertensive patients.Methods: This systematic review used the related elements to content chosen by the PRISMA statement and using specific keywords in the database; Ebscho, ScienceDirect, Elsevier, Sage Journals, Scopus, and ProQuest, limited to the last five years, 2016 to 2020, obtained 13 articles.Results: There were 13 articles that matched the inclusion criteria. There are various forms of intervention: from Short Message Services (SMS), smartphone applications, WeChat, and a combination of SMS with smartphone applications.Conclusion: Most studies report the value of customer satisfaction and high acceptance of each of the interventions provided. Mobile-based health interventions are effective in controlling blood pressure and can improve adherence to treatment in hypertensive patients.